Salmonella associated with captive and wild lizards in Malaysia - Cheng, B.; Wong, S.; Dykes, Gary (2014)
Reptiles are well known reservoirs of Salmonella and are capable of carrying the pathogen without showing any clinical signs. Previous studies have found a high prevalence of Salmonella and predominantly Salmonella enterica subspecies enterica (I) in lizards. This subspecies is also commonly associated with mammals and is responsible for most cases of human salmonellosis. Our study investigated the prevalence of Salmonella species and subspecies in captive and wild reptiles in and around Kuala Lumpur, Malaysia. A total of 60 lizard (12 captive and 48 wild) faecal samples were tested for the presence Salmonella. Approximately 36% of the lizards sampled carried Salmonella in their faeces with a significantly (p<0.05) higher prevalence in captive (83.3%) as compared to wild lizards (25%). Four Salmonella enterica subspecies were isolated, namely enterica (I), arizonae (IIIa), diarizonae (IIIb) and indica (VI). The higher prevalence of Salmonella in captive lizards highlights a risk of acquiring reptile-associated salmonellosis from handling lizards while the level of Salmonella in wild lizards suggests some risk associated with their presence in and around dwellings.